Existing drug treatments cannot significantly shorten the clinical cure time of children with COVID-19 - Mengting Li; Yang Wang; Hua Xu; Changlin Liu; Liang Shi; Qi Ye; Jun Wang; Sichan Li; Yan Mei; Liuliu Gao (Journal of Infection in Developing Countries)
Introduction: COVID-19 has become a global health security issue, it has caused more than half a million deaths worldwide so far, the treatment strategies are the most concerned issues for clinicians. In this study, the treatments and outcomes in 40 pediatric patients diagnosed with COVID-19 and treated with different drugs were evaluated.